Samuel McGowan papers - McGowan, Samuel, 1870-1934.
Correspondence, orders to duty, subject file, newspaper clippings, and other papers relating primarily to McGowan's duties as paymaster general, U.S. Navy Bureau of Supplies and Accounts (Supply Corps), and to his interest in changing naval regulations he regarded as discriminatory. Includes material pertaining to his service during World War I. Correspondents include Philip Andrews, Bernard M. Baruch, Charles J. Bonaparte, Thomas Jefferson Cowie, Josephus Daniels, Franklin D. Roosevelt, Benjamin R. Tillman, Woodrow Wilson, and McGowan family members.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Andrews, Philip, -- 1866-1945.; Baruch, Bernard M. -- 1870-1965.; Bonaparte, Charles J. -- 1851-1921 -- Correspondence; Cowie, Thomas Jefferson, -- 1857-1936 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Tillman, Benjamin R. -- 1847-1918 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; McGowan family -- Correspondence; United States. -- Navy -- Regulations; United States. -- Navy -- Supplies and stores; United States. -- Navy. -- Supply Corps; World War, 1914-1918.; Naval officers